Novel β-lactamase inhibitors: a therapeutic hope against the scourge of multidrug resistance - Watkins, Richard; Papp-Wallace, Krisztina M.; Drawz, Sarah M.; Bonomo, Robert A. (Frontiers in Microbiology, 2013)
The increasing incidence and prevalence of multidrug resistance (MDR) among contemporary Gram-negative bacteria represents a significant threat to human health. Since their discovery, β-lactam antibiotics are a major component of the armamentarium against these serious pathogens. Unfortunately, a wide range of β-lactamase enzymes have emerged that are capable of inactivating these powerful drugs. In the past 30 years, a major advancement in the battle against microbes has been the development of β-lactamase inhibitors, which restore the efficacy of β-lactam antibiotics (e.g., ampicillin/sulbactam, amoxicillin/clavulanate, ticarcillin/clavulanate, and piperacillin/tazobactam). Unfortunately, many newly discovered β-lactamases are not inactivated by currently available inhibitors. Is there hope? For the first time in many years, we can anticipate the development and introduction into clinical practice of novel inhibitors. Although these inhibitors may still not be effective for all β-lactamases, their introduction is still welcome. This review focuses on the novel β-lactamase inhibitors that are closest to being introduced in the clinic.